Indicadores do esgotamento sanitário de medianeira/pr frente aos desafios do novo marco legal do saneamento básico - Pastre, Fauston (2023)
Federal Law No. 11,445/2007 established guidelines for the policy of basic sanitation and universal access. The National Basic Sanitation Plan (PLANSAB), approved by Decree No. 8,141/2013, set goals for universalization in 20 years. The New Legal Framework for Basic Sanitation, Federal Law No. 14,026/2020, updates the previous legislation, aiming at the universalization of basic sanitation services to the Brazilian population, establishing goals of 99% access to drinking water and 90% sewage coverage by 2033, encouraging private investments in the sector. In this context, the present study developed an analysis of the historical and current indicators related to sanitary sewage made available by the National Sanitation Information System (SNIS) for the municipality of Medianeira/PR with a view to achieving the goal. Information from the SNIS was collected from 2014 to 2021 about the indicators of sanitary sewage in Medianeira and compared to the indices of the state of Paraná, the South Region and Brazil, as well as to the indicators of sewage collection and treatment of the other municipalities of the Foz do Iguaçu Microregion, in which the municipality of Medianeira is inserted. Through the historical series, the temporal evolution of the indicators IN015, IN024, IN056 and IN046 related to sewage collection and treatment were represented. Although Medianeira presented a historical liability with modest rates of sanitary sewage services, it revealed a positive evolution in sewage collection and treatment services, especially from 2019 onwards. With statistical resources, especially the Statgraphics software, projections of the indicators were made to observe whether the pace of evolution assumes the achievement of the 90% target by the year 2033. It was concluded that, with the strategies of the Sanitation Company of Paraná (SANEPAR), concessionaire of sanitation services, and maintaining the expected financial contributions as well as the pace already performed, the municipality of Medianeirse tends to achieve the goal established in the challenges of the New Legal Framework for Basic Sanitation within the stipulated period.